Molecular characterization of a large group of Mucopolysaccharidosis type IIIC patients reveals the evolutionary history of the disease. Issue 8 (22nd June 2019) - Martins, Carla; de Medeiros, Paula Frassinetti V.; Leistner‐Segal, Sandra; Dridi, Larbi; Elcioglu, Nursel; Wood, Jill; Behnam, Mahdiyeh; Noyan, Bilge; Lacerda, Lucia; Geraghty, Michael T.; Labuda, Damian; Giugliani, Roberto; et al.
Abstract: Mucopolysaccharidosis type IIIC (MPSIIIC) is a severe, rare autosomal recessive disorder caused by variants in the heparan‐α‐glucosaminide N‐acetyltransferase ( HGSNAT ) gene which result in lysosomal accumulation of heparan sulfate. We analyzed clinical presentation, molecular defects and their haplotype context in 78 (27 novel) MPSIIIC cases from 22 countries, the largest group studied so far. We describe for the first time disease‐causing variants in the patients from Brazil, Algeria, Azerbaijan, and Iran, and extend their spectrum within Canada, Colombia, Turkey, and the USA. Six variants are novel: two missense, c.773A>T/p.N258I and c.1267G>T/p.G423W, a nonsense c.164T>A/p.L55*, a splice‐site mutation c.494−1G>A/p.[P165_L187delinsQSCYVTQAGVRWHHLGSLQALPPGFTPFSYLSLLSSWNC, P165fs], a deletion c.1348delG/p.(D450fs) and an insertion c.1479dupA/p.(Leu494fs). The missense HGSNAT variants lacked lysosomal targeting, enzymatic activity, and likely the correct folding. The haplotype analysis identified founder mutations, p.N258I, c.525dupT, and p.L55* in the Brazilian state of Paraiba, c.493+1G>A in Eastern Canada/Quebec, p.A489E in the USA, p.R384* in Poland, p.R344C and p.S518F in the Netherlands and suggested that variants c.525dupT, c.372−2G>A, and c.234+1G>A present in cis with c.564‐98T>C and c.710C>A rare single‐nucleotide polymorphisms, have been introduced by Portuguese settlers in Brazil. Altogether, our results provide insights into the origin, migration roots and founder effects of HGSNAT disease‐causing variants, and reveal the evolutionary history of MPSIIIC. Abstract : Mucopolysaccharidosis type IIIC (MPSIIIC) is a severe, rare autosomal recessive disorder caused by variants in the heparan‐alpha‐glucosaminide N‐acetyltransferase ( HGSNAT ) gene which result in lysosomal accumulation of heparan sulfate. We analyzed clinical presentation, molecular defects and their haplotype context in 78 (27 novel) MPSIIIC cases from 22 countries, the largest group studied so far. The knowledge of distribution and frequency of MPSIIIC mutations in the populations enables faster detection of carriers and patients and, in the future, should lead to more efficient therapeutic approaches.